1692 The Aetiology of Acute Abdominal Pain in Children 2–12 Years of Age. (October 2012) - Kandamany, N; O'Neill, MB
Abstract : Background and Aims: Abdominal pain is common in childhood. This study evaluated abdominal pain in children aged 2–12 to determine the frequency of aetiologies. Methods: Patients between 2 and 12 years presenting to the Emergency Department over a 5 month period, with abdominal pain were included. Patients with chronic constipation, previous abdominal pain and previous gastrointestinal surgery were excluded. Data was collected prospectively utilising patient's charts and a pretested proforma on abdominal pain which contained diagnostic tips and prompts. Demographic data, referral source, symptom complex, examination findings, and diagnoses were noted. Patients with a diagnosis of constipation were followed up via telephone to confirm accuracy of diagnosis. Results: One hundred and thirteen patients were assessed .Aetiologies of abdominal pain were appendicitis 26 (23%), constipation 23 (20%), gastroenteritis 18 (16.5%), mesenteric adenitis 15 (13%), non specific abdominal pain(viral syndrome) 11 (10%), urinary tract infection 7 (6%), pneumonia 6 (5%), gastritis 5 (4.4%), acute asthma 2 (2%). Eighty four (75%) patients were referred by their family doctor. Patients diagnosed with constipation were contacted by telephone to confirm the diagnosis, with 18 (78%) agreeing. Conclusion: This study outlines the aetiology of abdominal pain in a paediatric population, three quarters of whom had been assessed by their family doctors prior to referral. Non gastrointestinal aetiologies need to be considered in the assessment.